HUBUNGAN KARAKTERISTIK, PENGETAHUAN DAN KEPERCAYAAN DIRI DENGAN SIKAP PERAWAT DALAM PELAKSANAAN PERAWATAN METODE KANGURU DI RS SWASTA TIPE C - Ni Ketut Adiana; Tuti Asrianti Utami; Paramitha Wirdani Ningsih (Jurnal Surya Muda, 2021)
Kangaroo Treatment Method (PMK) has benefits for mothers, babies with low birth weight (LBW), health workers and hospitals. NICU nurses and Perina are important factors in the successful implementation of PMK. The purpose of the study was to analyze the relationship between characteristics, knowledge, self-confidence and attitudes of nurses in the implementation of kangaroo care methods. Quantitative research, with a cross-sectional design using Chi-Square analysis and a total sampling of 60 respondents. The research was conducted from November 2019 to August 2020. This research was awarded an ethical qualification from the Sint Carolus STIK Health Research and Development Ethics Commission. The results of the study explained that most of the ages 17-35 years 39 (65%), D3 education 45 (75%), working > 5 years 38 (63.3%), not yet training 43 (71.7%), sufficient knowledge 40 ( 66.7%), confident 36 (60%) and have a good attitude 33 (55%) respondents. The results of Chi-Square analysis explained that there was a relationship between nurse age (p-value = 0.015), PMK training (p-value = 0.007) and there was no relationship between education (p-value = 0.653), length of work (p = 0.0095), knowledge (p-value = 0.099) and nurses' confidence (p-value = 0.244) with the attitude of nurses in implementing PMK in Type C Private Hospitals. This study recommends NICU nurses attend training on PMK so that nurses have a confident attitude in implementing PMK.